Ensayo exploratorio de métodos e interacciones de elementos en la aplicación de fertilizantes en el cultivo de maíz - Caceros, O. A. (2016)
Soil fertility studies have been conducted on the southern coastal plain of Guatemala for several years without showing significant response to phosphorus and sulfur fertilizer applications. In 1987, various exploratory trials were established to evaluate various methods of application for phosphorus, sulfur and nitrogen. Nitrogen sources evaluated were ammonium sulfate and urea. Beef manure was also evaluated in combination with ammonium sulfate. Various other N (as urea), P, S combinations were Included in this trial using CaSO4 as the S source. Banding phosphorus and nitrogen together especially ammonium sulfate with triple superphosphateprovided excellent response across locations. Due to the pH reduction within the NP band, H2PO4 availability at lower pH is Increased as has been demonstrated by others. Ammonium sulfate was by far a better N source compared to urea when applied alone and as such an S response was considered probable in 2 or the five locations. Gypsum applications were evaluated both as a source of sulfur and as an alternative to improving P availability by applying this source with triple superphosphate in a joint band. It was expected that the reaction products from applying gypsum and P together increase the P availability since the precipitated products (hypothesized, dicalcium phosphate dihydrate and dicalcium phosphate) would not be fixed and as such slowly available at low pH. Also If by combining triple superphosphate and gypsum in a joint hand, precipitation products DCIP and DCPD would reduce the amount of fertilizer P complexed with Fe and Al hydroxides and or allophane. Antagonistic Interactions were found between S and P which suggests that fertilizer P applications could induce S deficiencies (where S was not applied) since P may be replacing SO4 on the exchange complex of soils thought to have high anion exchange capacities and/or significant amounts of adsorbed SO4.